Effect of brushing simulation using remineralizing toothpaste on microhardness of anterior teeth - An in vitro study - Pawan Kumar Earasi , Dr. Dinesh Kumar, (Cuestiones de Fisioterapia, 2025)
Introduction: Brushing simulator machines are capable of running programmable three-dimensional brushing patterns. In microhardness testing, an indentation is made on the specimen by a diamond indenter through the application of a load. The aim of the study is to evaluate the effect of brushing simulation using remineralizing toothpaste on microhardness of anterior teeth.